Tumor necrosis factor- A and interleukin (IL)-1β, IL-6, and IL-8 Impair in vitro migration and induce apoptosis of gingival fibroblasts and epithelial cells, delaying wound healing - Basso, Fernanda G. [UNESP]; Pansani, Taisa N. [UNESP]; Turrioni, Ana Paula S. [UNESP]; Soares, Diana G. [UNESP]; De Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Wiley, 2016)
Background: Multiple factors affect oral mucosal healing, such as the persistence of an inflammatory reaction. The present study evaluates effects of tumor necrosis factor (TNF)-α and interleukin (IL)-1β, IL-6, and IL-8 on epithelial cells (ECs) and human gingival fibroblasts (GFs) in vitro. Methods: GFs and ECs were seeded in 96-well plates (1 · 104 cells/well) in plain culture medium (Dulbecco's modified Eagle's medium [DMEM]) containing 1% antibiotic/antimycotic solution and 10% fetal bovine serum, and incubated for 24 hours. Both cell lines were exposed for 24 hours to the following cytokines: 1) TNF-α (100 ng/mL); 2) IL-1β (1 ng/mL); 3) IL-6 (10 ng/mL); and 4) IL-8 (10 ng/mL). All cytokines were diluted in serum-free DMEM. Control cultures were exposed only to serum-free DMEM. Effects of exposure to inflammatory cytokines were determined by means of: 1) apoptosis (anexin V); 2) cell migration (wound healing assay); 3) inflammatory cytokine synthesis (enzyme-linked immunosorbent assay). Data were analyzed by Kruskal-Wallis and Mann-Whitney U tests (α = 0.05). Results: Increased apoptosis rates were noted when cells were exposed to inflammatory cytokines, except ECs exposed to IL-1β. Cell migration was negatively affected by all inflammatory cytokines for both cell lines. ECs and GFs exposed to IL-6 and IL-8 significantly increased synthesis of TNF-α and IL-1β. Conclusions: Demonstrated results indicate negative effects of tested inflammatory cytokines on ECs and GFs, inducing apoptosis and impairing cell migration. These results can justify delayed oral mucosa healing in the presence of inflammatory reaction.
Keywords: Apoptosis; Cell biology; Enzyme-linked immunosorbent assay; Epithelial cells; Fibroblasts; Interleukins; Wound healing